2016
DOI: 10.1093/arclin/acw057
|View full text |Cite
|
Sign up to set email alerts
|

Addenbrooke's Cognitive Examination-Revised: Effects of Education and Age. Normative Data for the Spanish Speaking Population

Abstract: The results show that both age and education have an important effect on ACE-R performance. Consequently, age and education should be taken into account when interpreting results in ACE-R to improve diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…This result is consistent with previous studies. 16,24 The optimal cut-off points for identifying MCI from HC, and MNCD from MCI were 71 and 62, respectively, which were found to be lower than the established cut-off values of the original ACE-III 19 and ACE-R. 16 Similarly, in Spanish 20 and Thai, 43 an identical lower cut-off values was reported. There are also studies in other languages, such as Chinese, 44 Cantonese, 45 and Korean, 46 where lower cut-offs were reported.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This result is consistent with previous studies. 16,24 The optimal cut-off points for identifying MCI from HC, and MNCD from MCI were 71 and 62, respectively, which were found to be lower than the established cut-off values of the original ACE-III 19 and ACE-R. 16 Similarly, in Spanish 20 and Thai, 43 an identical lower cut-off values was reported. There are also studies in other languages, such as Chinese, 44 Cantonese, 45 and Korean, 46 where lower cut-offs were reported.…”
Section: Discussionmentioning
confidence: 78%
“…21 Moreover, ACE-III has also been validated in other conditions, such as brain injury, stroke, and Parkinsonism, 18,22 yielding excellent diagnostic utility and helping clinicians to make more precise decisions about cognitive impairment and dementia. Several studies 24,25 have shown that the cut-off values of ACE-III are influenced by sociodemographic variables, such as age, 26 education, 20 and language. 27 Such factors play an important role when interpreting the suggested cut-off values as they affect the diagnostic accuracy in diverse populations.…”
Section: Introductionmentioning
confidence: 99%
“…Addenbrooke’s Cognitive Examination Revised Test (ACE-R) was performed in each patient before surgery and up to 30 days after. ACE-R is a diagnostic and screening instrument comprised of 5 domains: attention and orientation, memory, verbal fluency, language, and visuo-spatial abilities [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies with the ACE-R have shown that the cutoff points are influenced by sociodemographic variables 35,36. In several studies, with the ACE-III in several studies, the influence of demographic variables has been considered as seen to be an important variable to take into account when interpreting the suggested cutoff points and to improve diagnostic accuracy 9,38,40,44,46…”
Section: Variables To Consider In the Interpretation Of The Cutoff Pomentioning
confidence: 99%